Polyhydroxylated pyrrolidine and pyrrolizidine alkaloids from Hyancinthoides non-scripta and Scilla campanulata. - Kato, A; Adachi, I; Miyauchi, M; Ikeda, K; Komae, T; Kizu, H; Kameda, Y; Watson, A; Nash, R; Wormald, MR; Fleet, G; Asano, N (1999)
Aqueous ethanol extracts from the immature fruits and stalks of bluebell (Hyacinthoides non-scripta) were subjected to various ion-exchange column chromatographic steps to give 1,4-dideoxy-1,4-imino-D-arabinitol (1),2(R),5(R)-bis(hydroxymethyl)-3(R),4(R)-dihydroxypyrrolidine (DMDP) (2), 6-deoxy-6-C-(2,5-dihydroxyhexyl)-DMDP (3),2,5-dideoxy-2,5-imino-DL-glycero-D-manno-heptitol (homoDMDP)(4),homoDMDP-7-O-apioside (5), homoDMDP-7-O-beta-D-xylopyranoside (6), (1S*,2R*,3R*,5R*,7aR*)-1,2-dihydroxy-3,5- dihydroxymethylpyrrolizidine (7), and (1S*,2R*,3R*,5R*,6R*,7R*,7aR*)-3-hydroxymethyl-5-methyl-1,2,6,7 tetrahydroxypyrrolizidine (8). Bulbs of Scilla campanulata (Hyacinthaceae) yielded (1S*,2R*,3R*,5S*,7aR*)-1,2-dihydroxy-3,5-dihydroxy-methylpyrrol izidine (9) in addition to compounds 1-7. Compounds 3,6,7,8, and 9 are new natural products. Compound 4 is a potent competitive inhibitor with K(i) values of 1.5 microM for Caldocellum saccharolyticum beta-glucosidase and 2.2 microM for bovine liver beta-galactosidase. The 7-O-beta-D xyloside 6 was a stronger competitive inhibitor than 4 of C saccharolyticum beta-glucosidase and rat intestinal lactase, with K(i) values of 0.06 and 0.07 microM, respectively, but a weaker inhibitor of bovine liver beta-galactosidase. Furthermore, compound 4 is also a competitive inhibitor (K(i) = 1.8 microM) of porcine kidney trehalase, but 6 was inactive against this enzyme.